“All you’ve got to do is stop”: A Qualitative Examination of Gambling Stigma and Discrimination from the Perspective of Lived Experience - Elizabeth Killick; Clare Wyllie; Alexander Källman; Michelle Potiaumpai (Critical Gambling Studies, 2024)
People with lived experience have drawn attention to gambling stigma as a harm in itself, justifying discrimination and exacerbating other harms. The gambling establishment’s response has reproduced individual responsibility by reducing stigma to a barrier to help-seeking. More recently, adapting to critiques of individual responsibility, the gambling establishment has expanded the issue to one of services and society. This paper identifies the structural dynamics that drive gambling stigma and discrimination from the perspective of lived experience. Semi-structured interviews were conducted with adults in Great Britain who had experienced gambling harm (n = 40). Several key themes were identified: (1) Harmless fun and individual responsibility; (2) Comparison with substance use; (3) The role of money; (4) Lack of parity in government policy; (5) Stereotypes of “typical” gamblers. The findings show the fundamental driver of stigma is the way commercial gambling functions and is enabled to function by the state, thus perpetuating the very conditions producing stigma in the first place. Stigma-reduction strategies that focus on changing individual behaviour or public information campaigns that tell people to get help early are insufficient: they are just another version of “responsible gambling,” where the individual is expected to do everything. Change requires addressing the unique features of gambling harm, stigma and discrimination, and the position the U.K. government allows commercial gambling to occupy.